FLAX AND FALSE FLAX AS IMPORTANT SOURCES OF ESSENTIAL OMEGA-3 FATTY ACIDS - Lykhochvor В.; Petrychenko В.; Andrushko О.; Lykhochvor Д. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Field studies were carried out at the experimental field of Lviv National Environmental University on dark gray podsolized light loamy soil. The study focused on spring oilseeds including False flax (Camelina sativa L.), Flax oil (Linum usitatissimum L.), Spring rape (Brassica napus oleifera annua Metzd.), White mustard (Sinapis alba L.), and Blue mustard (Brassica juncea Czern.) to determine their productivity, oil content, and quality. The research found that spring rapeseed had the highest seed yield at 2.82 t/ha, followed by spring false flax at 2.68 t/ha, and oilseed flax at 2.34 t/ha. It was also found that applying insecticides and fungicides when growing false flax is impractical, although without them, achieving a high rapeseed yield is almost impossible. Thus, it results in a reduced cost of false flax seeds glowing compared to rapeseed. The study established that flax had the highest oil content at 52.2%, followed by blue mustard at 45.8%, and false flax at 45.0%. The highest oil yield was from rapeseed, false flax, and flax at 1.21–1.25 t/ha. Physiologically, flax and false flax are the most valuable due to their high content of linolenic Omega-3 acid, which should be utilized more widely in human nutrition for therapeutic, dietary, and preventive purposes. In terms of linolenic Omega-3 acid content, oilseed flax (56.2 %) and false flax (48.8%) had the advantage. Blue mustard had the highest linoleic acid content, while spring rape had the highest oleic acid content at 60.5%. The experiment found that the content of erucic acid, which is harmful to animals and humans, was within permissible limits for false flax (3.0%), spring rape (0.2%), and oilseed flax (0.2%), but exceeded limits for blue mustard (21.4%) and white mustard (44.5%). The study did not establish a clear relationship between oil content and yield, but identified different types of dependence. Rapeseed had the highest yield with average oil content, white mustard had low yield and the lowest oil content, blue mustard had significantly higher oil content despite low yield, and oilseed flax had the highest oil content with an average yield. False flax had a relatively high yield and an average oil content.